2011
DOI: 10.1007/s12975-011-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Are Underlying Assumptions of Current Animal Models of Human Stroke Correct: from STAIRs to High Hurdles?

Abstract: Animal models of acute ischemic stroke have been criticized for failing to translate to human stroke. Nevertheless, animal models are necessary to improve our understanding of stroke pathophysiology and to guide the development of new stroke therapies. The rabbit embolic clot model is one animal model that has led to an effective therapy in human acute ischemic stroke, namely tissue plasminogen activator (tPA). We propose that potential compounds that demonstrate efficacy in non-rabbit animal models of acute i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 72 publications
0
34
0
1
Order By: Relevance
“…DW-MRI on a 3 T clinical MR scanner can be used to reliably quantify infarction volume, but not T2-FLAIR MRI. There remains wide interest in the use of rabbit models for translational stroke research, and recent work continues to characterize the RSCEM model 9 10. However, studies of cellular biology and neuroimaging of acute reversible and irreversible cerebral ischemia would benefit from a rabbit model in which LVO can be induced reproducibly, easily confirmed, and in which the time of occlusion and revascularization can be precisely controlled.…”
Section: Discussionmentioning
confidence: 99%
“…DW-MRI on a 3 T clinical MR scanner can be used to reliably quantify infarction volume, but not T2-FLAIR MRI. There remains wide interest in the use of rabbit models for translational stroke research, and recent work continues to characterize the RSCEM model 9 10. However, studies of cellular biology and neuroimaging of acute reversible and irreversible cerebral ischemia would benefit from a rabbit model in which LVO can be induced reproducibly, easily confirmed, and in which the time of occlusion and revascularization can be precisely controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke clinicians who routinely manage stroke victims in an emergency room would dispute the fact that an embolic stroke results from the movement of a blood clot into the brain [9, 10, 7]. The recent positive intravascular embolectomy studies reported from MR. CLEAN, ESCAPE, EXTEND-IA, SWIFT PRIME, and REVASCAT [57, 60, 58, 59, 65] emphasize that the embolic stroke event can now be treated using the new generation of devices, in addition to rt-PA as described above.…”
Section: B) Mechanical Embolectomymentioning
confidence: 99%
“…Yes [See(20, 21, 40, 41)]. Clinical trial enrollment data derived from randomized and blinded clinical trial such as the original NINDS tPA clinical trial report(42) shows that the patient population included in the placebo control group had NIHSS scores of 1–32 and the active drug group had a range from 1–37(42).…”
Section: The Benefits Of Therapy Testing In the Rscem Bioassaymentioning
confidence: 99%